Environmental relationships of the vascular flora alongside the railway tracks between haydarpaşa and gebze (Istanbul-Kocaeli/ Turkey) - (:unkn) unknown (Triveni Enterprises, 2015)
The vascularflora alongside the railway track between Haydarpasa and Gebze in Turkey was investigated and the floristic features of the study area are presented here. The investigation was undertaken during 2003-2009. Intotal 194 plant taxa were determined. Out of these 174 were naturally growing and 20 were exotics and cultivated. Native taxa within the flora belonged to 135 genera and 50 families, exotic and cultivated taxa belonged to 20 genera and 15 families. The members of Dicotyledonae constituted of 82.76% and Monocotyledonae 16.09% ofthe native taxa. The highest number of these taxa belonged to Asteraceae family (25 species), while the exotics were from Rosaceae (5 species). The plant distributional features, phytogeographical elements, life forms, archaeophytes and neophytes and status of invasive plants have also been included.
Keywords: Istanbul; Kocaeli; Railway trackflora; Turkey